Biodiversitas dan sebaran mikroalga berbasis sistem informasi geografis (SIG) di Perairan Selatan Kabupaten Malang, Jawa Timur - Umi Zakiyah; Mulyanto Mulyanto (Depik, 2020)
The coastal region is a meeting point of land and sea. The coastal area utilization has developed intensively, which causes the sustainability or capacity of coastal ecosystems, and the pollution potential in this area exceeded due to various human activities. This condition affects the existence of microalgae, which play an important role not only in the food chain in the aquatic environment but also in humans at the end. This research was carried out in Sendang Biru Waters, South Malang Regency. The purpose of this study was to map and determine the biodiversity as well as the distribution of microalgae in coastal waters using in situ data. The data were analyzed using geographic information system techniques in the form of microalgae distribution and biodiversity maps. The results showed that the microalgae identified from the genera Chaetoceros and Navicula showing the highest frequency. The biodiversity index value at station 1 was 3,312, at station 2 was 3,184. These values indicate that the Sendang Biru waters were highly diverse in microalgae composition. The results of the temperature-water quality parameters are 27-29 ° C, salinity 32-35 ppt, and pH 7.8-8.2. The range of nitrate nutrients ranges from 0.0142 to 0.082 mg/l, while phosphate from 0.024 to 0.074 mg/l, silica showed values between 1.249 to 1.393 mg/l. Based on the analysis of chlorophyll-a, the range of chlorophyll-a values was between 1.773-1.777 mg/l. All parameters of water quality were classified as suitable for microalgae growth. Therefore, the microalgae biodiversity in this location can still be considered relatively high.Keywords:Coastal AreaBiodiversityMicroalgaeABSTRAKWilayah pesisir merupakan tempat bertemunya daratan dan lautan. Pemanfaatan wilayah pesisir secara intensif mengakibatkan terlampauinya daya dukung atau kapasitas berkelanjutan dari ekosistem pesisir dan meningkatnya potensi pencemaran pada perairan pesisir yang ditimbulkan dari berbagai aktivitas manusia. Pencemaran ini akan mempengaruhi keberadaan mikroalga yang mempunyai peranan penting bukan saja dalam rantai makanan di perairan namun manusia juga pada akhirnya.  Penelitian ini dilakukan di Perairan Sendang Biru, Kabupaten Malang. Tujuan penelitian untuk mengetahui dan memetakan biodiversitas dan sebaran mikroalga di perairan pantai selatan Kabupaten Malang, dengan data in situ. Data dianalisis menggunakan peta yang dihasilkan dari teknik sistem informasi geografis dari biodiversitas dan sebaran mikroalga. Hasil penelitian menunjukkan bahwa mikroalga yang teridentifikasi genus Chaetoceros dan Navicula memiliki kelimpahan tertinggi. Nilai index diversitas pada stasiun 1 adalah 3,312, sedangkan pada stasiun 2 adalah 3,184. Nilai tersebut menunjukkan bahwa mikroalga di perairan Sendang Biru memiliki keanekaragaman tinggi. Hasil parameter kualitas air suhu yaitu 27-29 0C, salinitas 32-35 ppt, dan pH 7,8-8,2. Kisaran nutrien nitrat adalah 0,0142 – 0,082 mg/l, fosfat 0,024 – 0,074 mg/l, dan silica berkisar 1.249 – 1.393 mg/l. Berdasarkan hasil analisis klorofil-a didapatkan kisaran nilai klorofil-a 1,773-1,777 mg/l. Seluruh parameter kualitas air masih tergolong dalam kategori baik untuk kehidupan mikroalga sehingga dapat disimpulkan biodiversitas mikroalga di lokasi penelitian relatif tinggi.Kata kunci:Wilayah PesisirKeanekaragamanMikroalga